Politik Pendidikan di Indonesia di Masa Pandemi: Respon Mahasiswa Terhadap Pembelajaran Jarak Jauh - Sulaeman, Kirana Mahdiah; Ramaditya, Fauzan; Putra, Haelvyn Pratagrahana (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
Abstract The COVID-19 pandemic has an impact not only on public health, but also on the education system. With the government's advocacy of physical distancing, students from various universities in Indonesia are forced to adopt the Distance Learning method or online learning. However, along with the extension of the physical distancing recommendation, there was anxiety among students regarding the effectiveness of Distance Learning. In fact, according to a survey from the Director General of Higher Education, 70% of lecturers and students are satisfied with the Distance Learning method. This study explores qualitatively how students actually respond to distance learning. Researchers interviewed a number of students spread across three universities in Indonesia. The finding of this study is that although most of the participants experienced an increase in their academic achievement index scores, all participants felt uncomfortable with distance learning and preferred the normal teaching-learning process. This inconvenience is caused by many constraints such as cost and access to the internet, inadequate teaching methods for lecturers, lack of interaction and learning motivation, lack of support from the surrounding environment for learning, and technical problems. This finding is analyzed using the perspective of politics of education. The authors argue that the implementation of politics of education in Indonesia is still not ideal due to the sudden pandemic.